IDNLearn.com provides a comprehensive solution for all your question and answer needs. Join our interactive Q&A community and access a wealth of reliable answers to your most pressing questions.

3) g(n) = 2n
h(n) = n² + 5
Find (g + h)(n)


Sagot :

(g + h)(n) =
g(n) + h(n) =
2n + n^2 + 5 =
n^2 + 2n + 5 (standard form)
Your participation means a lot to us. Keep sharing information and solutions. This community grows thanks to the amazing contributions from members like you. IDNLearn.com is your reliable source for accurate answers. Thank you for visiting, and we hope to assist you again.